Nano-Carbon Coating Layer Prepared by the Thermal Evaporation of Fullerene C-60 for Lithium Metal Anodes in Rechargeable Lithium Batteries - Arie, Arenst Andreas; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2011)
A nano carbon coating layer was prepared by the thermal evaporation of fullerene C-60 on the surface of lithium metal anodes for rechargeable lithium batteries. The morphology and structure of the carbon layer was firstly investigated by Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The effects of the nano-carbon coating layer on the electrochemical performance of the lithium electrode were then examined by charge discharge tests and impedance spectroscopy. Raman spectra of carbon coating layer showed two main peaks (D and G peaks), indicating the amorphous structure of the film. A honey comb-like structure of carbon film was observed by TEM photographs, providing a transport path for the transport of lithium ions at the electrode/electrolyte interface. The carbon coated lithium electrodes exhibited a higher initial coulombic efficiency (91%) and higher specific capacity retention (88%) after the 30th cycle at 0.2 C-rate between 3.4 and 4.5 V. Impedance measurements showed that the charge transfer resistance was significantly reduced after cycle tests for the carbon coated electrodes, revealing that the more stable solid electrolyte (SEI) layer was established on their surface. Based on the experimental results, it suggested that the presence of the nano-carbon coating layer might suppress the dendritic growth on the surface of lithium metal electrodes, as confirmed by the observation of SEM images after cycle tests.
Keywords: ELECTROLYTE INTERFACE; ORGANIC ELECTROLYTE; THIN-FILMS; LI; INSERTION; CO2